Anti-acne potential of Haematococcus pluvialis: GC–MS profiling and antibacterial activity of n–hexadecanoic acid and α–tocopherol (Journal of Advanced Veterinary and Animal Research, 2025)
Objective: This study explores the bioactive compounds in Haematococcus pluvialis and their potential as anti-acne agents through gas chromatography–mass spectrometry (GC–MS) analysis and disc diffusion assays. Materials and Methods: 3.3 gm of H. pluvialis was extracted and tested against three acne-causing pathogens: Propionibacterium acnes, Staphylococcus aureus, and Staphylococcus epidermidis, under varying extract concentrations. Results: The GC–MS analysis detected several bioactive compounds in the extract, including fatty acids (e.g., n-hexadecanoic acid and linoleic acid esters), polysaccharides, vitamins, aromatic compounds, and diterpenoids. Fatty acids and vitamin compounds dominated, comprising 72.20% of the extract, with alpha-tocopherol and its derivatives as prominent components. Antimicrobial activity was assessed using the disc-diffusion method. The extract demonstrated notable antibacterial effects, particularly at 10 ppm, achieving inhibition zones of 18.0 ± 2.0 mm against P. acnes, 19.9 ± 1.7 mm against S. aureus, and 19.5 ± 4.7 mm against S. epidermidis. These zones of inhibition were classified as intermediate. Conclusion: The results indicate that microalgae from the Chlorophyceae class are more effective against Gram-positive than Gram-negative bacteria. These findings emphasize the potential of bioactive compounds as anti-acne agents, suggesting they could serve as substitutes for antibiotics.J. Adv. Vet. Anim. Res., 12(3): 988–1000, September 2025http://doi.org/10.5455/javar.2025.l958